2015
DOI: 10.3109/00207454.2015.1057636
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase subtilisin/kexin type 9 (PCSK9) in lipid metabolism, atherosclerosis and ischemic stroke

Abstract: Proprotein convertase subtilisin/kexin 9 (PCSK9) is the ninth member of the proprotein convertase family. It is an important regulator of cholesterol metabolism. PCSK9 can bind to low-density lipoprotein receptors (LDLRs) and induce the degradation of these receptors through the endosome/lysosome pathway, thus decreasing the LDLR levels on the cell surface of hepatocytes, resulting in increased serum low-density lipoprotein cholesterol (LDL-C) concentrations. Recent studies have found that gene polymorphisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…This neutral effect on cognition has been recently reported by the EBBINGHAUS study, Drugs (even apparently specific monoclonal antibodies) can exert actions on more than one protein if such targets belong to a family of structurally similar proteins. PCSK9, for example, is one of nine related proprotein convertases (32). Such 'off-target' actions, whether beneficial or deleterious, would not be shared by variants in the gene encoding the target of interest.…”
Section: Discussionmentioning
confidence: 99%
“…This neutral effect on cognition has been recently reported by the EBBINGHAUS study, Drugs (even apparently specific monoclonal antibodies) can exert actions on more than one protein if such targets belong to a family of structurally similar proteins. PCSK9, for example, is one of nine related proprotein convertases (32). Such 'off-target' actions, whether beneficial or deleterious, would not be shared by variants in the gene encoding the target of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the mechanism of ischemic stroke has not been fully elucidated and may involve a complex interplay between environmental and genetic factors, such as polymorphic variants of the genes that regulate cholesterol and lipid biosynthesis or degradation 2 . Emerging lines of evidence revealed that lectin-like oxidized-low density lipoprotein receptor-1 (LOX-1) and proprotein convertase subtilisin/kexin 9 (PCSK9) play critical roles in hyperlipidemia and atherogenesis development, that ultimately leads to ischemic stroke 3 4 .…”
mentioning
confidence: 99%
“…PCSK9 binds to low density lipoprotein receptor (LDLR) and disrupts its endocytic recycling or directs it for lysosomal degradation 16 17 . Therefore, PCSK9 activation can downregulate LDLR expression and inhibit the uptake of LDL-C, which in turns leading to hypercholesterolemia and ischemic stroke event 4 18 .…”
mentioning
confidence: 99%
“…The gene which encodes for the PCSK9 is located on chromosome 1 [52,53] and encodes for the member of the subtilisin-like proprotein convertase family that activates other proteins, and its coding region is comprised of 13 exons [52]. In 2003, through the protein BLAST program [54], a putative convertase called neural apoptotic-regulated convertase 1 (NARC-1), which belongs to the proteinase L subfamily of subtilases, was identified [55].…”
Section: Proprotein Convertase Subtilisin/kexin Type 9 (Pcsk9)mentioning
confidence: 99%